PENGGUNAAN PLATFORM GAMES ONLINE GARTIC.IO DALAM PENDIDIKAN AGAMA KRISTEN - Anita Rosriyanti Sofia Ratu Edo; Leny Asrita Gokun Peong; Simson Haris Malla; Jesica Lidya Romaito (Bethel Press, 2021)
Educational games have become an essential aspect of modern education. Student engagement in learning is crucial, as teaching should involve teachers and active participation from students. This study discusses the teacher's role in developing innovative and effective teaching methods through educational games. With the advancement of technology, educational games are increasingly relevant for creating engaging and interactive learning experiences. This research employs a descriptive qualitative method with a literature review approach to collect data from various relevant sources. The results show that educational games can enhance students' motivation, engagement, and understanding of lesson material. These games also support various learning styles and help develop essential skills such as problem-solving, critical thinking, teamwork, and creativity. Furthermore, the study emphasizes the importance of teacher creativity in designing and delivering lesson materials and the challenges faced in implementing educational games in the classroom. Support from the government, schools, and the community is necessary to overcome these barriers and maximize the benefits of educational games in education. With the right approach, educational games and teacher creativity can create more meaningful and enjoyable student learning experiences.